Effectiveness of Multimodal Treatment for Young People With Body Dysmorphic Disorder in Two Specialist Clinics. Issue 5 (September 2022) - Rautio, Daniel; Gumpert, Martina; Jassi, Amita; Krebs, Georgina; Flygare, Oskar; Andrén, Per; Monzani, Benedetta; Peile, Lauren; Jansson-Fröjmark, Markus; Lundgren, Tobias; Hillborg, Maria; Silverberg-Mörse, Maria; et al.
Highlights: The largest effectiveness study of young people with BDD to date. CBT delivered flexibly, in combination with SSRIs, is effective for adolescent BDD. Treatment gains were maintained up to 1 year after treatment. BDD symptoms continued to improve throughout the follow-up. No consistent baseline predictors of BDD treatment outcome were identified. Abstract: Body dysmorphic disorder (BDD) typically originates in adolescence and is associated with considerable adversity. Evidence-based treatments exist but research on clinical outcomes in naturalistic settings is extremely scarce. We evaluated the short- and long-term outcomes of a large cohort of adolescents with BDD receiving specialist multimodal treatment and examined predictors of symptom improvement. We followed 140 young people (age range 10–18) with a diagnosis of BDD treated at two national and specialist outpatient clinics in Stockholm, Sweden ( n = 96) and London, England ( n = 44), between January 2015 and April 2021. Participants received multimodal treatment consisting of cognitive behavior therapy and, in 72% of cases, medication (primarily selective serotonin reuptake inhibitors). Data were collected at baseline, posttreatment, and 3, 6, and 12 months after treatment. The primary outcome measure was the clinician-rated Yale-Brown Obsessive-Compulsive Scale Modified for BDD, Adolescent version (BDD-YBOCS-A). Secondary outcomes included self-reported measures of BDD symptoms, depressive symptoms, and global functioning. Mixed-effects regression models showed that BDD-YBOCS-A scores decreased significantly from baseline to posttreatment (coefficient [95% confidence interval] = -16.33 [-17.90 to -14.76], p <0.001; within-group effect size (Cohen's d ) = 2.08 (95% confidence interval, 1.81 to 2.35). At the end of the treatment, 79% of the participants were classified as responders and 59% as full or partial remitters. BDD symptoms continued to improve throughout the follow-up. Improvement was also seen on all secondary outcome measures. Linear regression models identified baseline BDD symptom severity as a predictor of treatment outcome at posttreatment, but no consistent predictors were found at the 12-month follow-up. To conclude, multimodal treatment for adolescent BDD is effective in both the short- and long-term when provided flexibly within a specialist setting. Considering the high personal and societal costs of BDD, specialist care should be made more widely available.